2020
DOI: 10.3390/su12051921
|View full text |Cite
|
Sign up to set email alerts
|

Energy Performance Evaluation of a Desiccant Air Handling System to Maximize Solar Thermal Energy Use in a Hot and Humid Climate

Abstract: A desiccant air handling unit is one of the major types of dehumidification handling systems and requires hot water or hot air to regenerate sorption materials. If solar thermal energy is used as the heat source for regeneration, in general, a backup electrical heater, backup boiler, or combined heat and power (CHP) is installed in order to maintain a stable hot water supply. In this study, effective control is proposed for a desiccant air handling system that uses solar thermal energy (flexible control), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The proposed air conditioning unit was able to ensure thermal and humidity comfort over 90% of the time in an arid climate, whereas only 50% to 60% comfort time share was experienced in a warm humid climate. A solar-based heat pump-assisted system was modelled by Luo et al [31] in Taiwan, and it was found to be suitable for application in such a warm and humid climate; the results were corroborated by Ukai et al [32] who also incorporated the effect of optimised system regulation.…”
Section: Introductionmentioning
confidence: 86%
“…The proposed air conditioning unit was able to ensure thermal and humidity comfort over 90% of the time in an arid climate, whereas only 50% to 60% comfort time share was experienced in a warm humid climate. A solar-based heat pump-assisted system was modelled by Luo et al [31] in Taiwan, and it was found to be suitable for application in such a warm and humid climate; the results were corroborated by Ukai et al [32] who also incorporated the effect of optimised system regulation.…”
Section: Introductionmentioning
confidence: 86%